On relationship - Krishnamurti, J. (India : Krishnamurti foundation, 1992)
On Relationship is one of a series of theme books put together from the talks and writings of J. Krishnamurti. In 1950, Krishnamurti said: 'If we are concerned with our own lives, if we understand our relationship with others, we will have created a new society; otherwise we will put perpetuate the chaotic mess and confusion.' Providing a far-reaching basis for solving many of the world's crises, this book brings together Krishnamurti's most essential teachings on the individual's relationship to other people, to society, and to life itself. The renowned teacher makes it clear that the way we handle personal crises and relationships links us to the problems of all people and has a larger, global meaning. Ending the causes of war, for instance, cannot start without our seeing the need for real respect within the family and for all others.
Includes bibliographical references
Keywords: Interpersonal relations; Sociale relaties